Heterosis, inbreeding depression and heritability for yield and yield components in cowpea - A.R. Pathak; M.R. Naik and; H.K. Joshi (Electronic Journal of Plant Breeding, 2017)
A field experiment was undertaken with a view to know the extent of heterosis, inbreeding depression, heritability and genetic advance for yield and yield components in cowpea [Vigna unguiculata (L.) Walp.]. Six generations viz., P1, P2, F1, F2, BC1 and BC2 of eight crosses involving sixteen diversified cultivars of cowpea [Vigna unguiculata (L.) Walp.] were evaluated for yield and its traits. Significant positive heterosis for seed yield per plant and its related traits followed by significant inbreeding depression indicated major role of non-additive gene actions in the inheritance of seed yield per plant and its attributes. For seed yield per plant top three heterotic crosses were cross II (GC-4 x Pusa komal) followed by cross VIII (Cowpea sabra x Waghai krushi) and cross I (GC-3 x Pusa falguni). High heritability coupled with high genetic advance for cross I (GC-3 x Pusa falguni) and high heritability coupled with moderate genetic advance for cross II (GC-4 x Pusa komal), cross III (GC-5 x Anand cowpea), cross IV (W-203-3 x W-3-1) and cross V (W-502-2 x W-3-2) for seed yield per plant indicated heritability was due to additive gene effects. Involvement of both additive and non-additive gene effects suggested that it would be desirable to follow cyclic method of breeding.